Computer automated analysis of morphometric characteristics of epididymal spermatozoa of spotted deer (Axis axis) - SUNDARARAMAN, M N; SUBRAMANIAN, K S; MEENAKSHISUNDARAM, A; JOHN EDWIN, M (The Indian Journal of Animal Reproduction, 2023)
The morphometric characteristics of epididymal spermatozoa of spotted deer (Axis axis) was analysed using a computerassisted semen analyzer (CASA). The smears prepared from epididymal spermatozoa were stained with Stat III Andrology stainand the morphometric parameters were measured on CASA. The mean (± SE) values for m~jor axis (μm), minor axis (μm),elongation (per cent), head area (μm2), perimeter(μm) and tail length (μm) were recorded as 8.35 ± 3.24, 4.92 ± 2.31, 58.8 ± 0.24,33.41 ± 0.26, 21.96 ± 7.87 and 51.9 ± 0.64, respectively.
Keywords: Spotted deer (Axis axis); spermatozoa; morphometry; CASA